PEMBUDIDAYAAN JAMUR KUPING PADA KAYU TURI (Sesbania grandiflora (L.) Poir.) - Sihati Suprapti (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Ear mushroom (Auricularia polytrica) was cultivated on turi logs. The logs were kept slanted on an angle of ± 60° with bamboo supports before being inoculated with spawn of ear mushroom at Bogor. The mature mushroom were harvested daily after the growth of the fruiting body.The logs start producing mushroom two months after inoculation. After seven month of observation, the average total yield per log was 0.589 kg (at the base of trunk), 0.885 kg (middle of trunk), 0.648 kg (top of trunk) and 0.141 kg (branch).The total yield during seven month observation was obtained from the base of trunk (61.864 kg), middle of trunk (179.120 kg), top of trunk (203.656 kg) and branch (74.778 kg) per m3 of log.